The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1177/004908571004000202
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Care among Tribes of Central India

Abstract: This article highlights the state of maternal and newborn health and traditional practices observed by tribes of central India. The study presents a review of micro level studies conducted in undivided Madhya Pradesh state and wherever needed these results are supported or compared with the national and state level statistics. The study demonstrates that utilisation of maternal and child health services is very poor among the tribes of central India. Clinically acceptable maternal and newborn care practices fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…prelacteal feeds were given for all home and institutional births. Many studies from India and other South Asian countries have indicated that women commonly wait for several days after birth to begin breast-feeding, avoid giving colostrum, or supplement breast-feeding with other food or liquids [28,29]. However findings from present study compare poorly with recent studies from Nepal, Pakistan and Bangladesh which shows early breast-feeding initiation rates of 91 percent, 73 percent and more than 90 percent respectively [25,30,31].…”
Section: Discussioncontrasting
confidence: 97%
“…prelacteal feeds were given for all home and institutional births. Many studies from India and other South Asian countries have indicated that women commonly wait for several days after birth to begin breast-feeding, avoid giving colostrum, or supplement breast-feeding with other food or liquids [28,29]. However findings from present study compare poorly with recent studies from Nepal, Pakistan and Bangladesh which shows early breast-feeding initiation rates of 91 percent, 73 percent and more than 90 percent respectively [25,30,31].…”
Section: Discussioncontrasting
confidence: 97%
“…These spatial or geographic differentials in infant mortality may be due to the differences in their socio-economic development and/or cultural factors. These findings are in accordance with previous studies (Dhar, 2013;Marwar and Jain, 1997;NSSO, NSO, and MOSPI, 2011;Pandey, 1988;Pandey and Tiwari, 2001;Sahu, Nair, Singh et al, 2015;Sharma, 2010;van Dillen, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Women from villages near the health centers utilize primary health centers only in case of emergency (Marwar and Jain, 1997). One study demonstrated that the utilization of maternal and child healthcare services is very limited among the tribes of Madhya Pradesh (Sharma, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Oil massage of newborn is a common practice in Asian region. [ 23 , 24 ] It is believed to help in the physical development of the baby. In our study, nearly one-fourth of newborns were given bath on the day of birth.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 32 , 33 ] Traditional healers are preferred because of easy availability, poor access to health facility, and financial barriers. [ 23 , 34 , 35 ] At times, such traditional and household-level constraints cause delay in utilization of appropriate medical care thereby increasing the risk of neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%